Strengthening Case and Project Methods for Improvement Competencies of Vocational Students - Yuliana, Gatot; Aunnurahman; Herawati, Henny; Sulistyarini; Maryuni, Sri; Rusdiyono; Bistari; Nurdini, Asriah; Samodra, Y. Touvan Juni; Tiara (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2024)
Improving the quality of education is a challenging task. Schools serve as a pathway to prepare students to become responsible members of society. On the other hand, vocational schools focus on providing practical skills that can be useful in real life situations. Teachers play a crucial role in shaping the education process for students. In order to make students proficient in their respective fields of study, teachers carry out advocacy programs in classrooms. Community service activities are aimed at helping vocational school teachers enhance the quality of education by using project and problem-based learning. The implementation of these services is achieved through interactions and guidance on learning models for vocational school teachers. The results of this PKM activity have been overwhelmingly positive. Participants found the activity to be 100% useful, which helped them strengthen their competencies. The material presented was highly appropriate and of great quality.